2013
DOI: 10.1007/s13353-013-0154-0
|View full text |Cite
|
Sign up to set email alerts
|

11p13 deletions can be more frequent than the PAX6 gene point mutations in Polish patients with aniridia

Abstract: Aniridia is a rare, bilateral, congenital ocular disorder causing incomplete formation of the iris, usually characterized by iris aplasia/hypoplasia. It can also appear with other ocular anomalies, such as cataracts, glaucoma, corneal pannus, optic nerve hypoplasia, macular hypoplasia, or ectopia lentis. In the majority of cases, it is caused by mutation in the PAX6 gene, but it can also be caused by microdeletions that involve the 11p13 region. Twelve unrelated patients of Polish origin with a clinical diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 13 publications
2
16
0
1
Order By: Relevance
“…9 MLPA analysis revealed large deletions affecting PAX6 and/or neighboring genes in 30 probands including 24 sporadic and 6 familial cases (n = 12 patients); 17 different deletions ranging from at least 7.5 Mb to 3 kb were detected and designated Del1-Del17 The non-WAGR patients showed similar defects to those with truncating mutations, which is consistent with other reports. 9 MLPA analysis revealed large deletions affecting PAX6 and/or neighboring genes in 30 probands including 24 sporadic and 6 familial cases (n = 12 patients); 17 different deletions ranging from at least 7.5 Mb to 3 kb were detected and designated Del1-Del17 The non-WAGR patients showed similar defects to those with truncating mutations, which is consistent with other reports.…”
Section: Large Deletionssupporting
confidence: 86%
See 2 more Smart Citations
“…9 MLPA analysis revealed large deletions affecting PAX6 and/or neighboring genes in 30 probands including 24 sporadic and 6 familial cases (n = 12 patients); 17 different deletions ranging from at least 7.5 Mb to 3 kb were detected and designated Del1-Del17 The non-WAGR patients showed similar defects to those with truncating mutations, which is consistent with other reports. 9 MLPA analysis revealed large deletions affecting PAX6 and/or neighboring genes in 30 probands including 24 sporadic and 6 familial cases (n = 12 patients); 17 different deletions ranging from at least 7.5 Mb to 3 kb were detected and designated Del1-Del17 The non-WAGR patients showed similar defects to those with truncating mutations, which is consistent with other reports.…”
Section: Large Deletionssupporting
confidence: 86%
“…The location and type of mutation did not appear to be predictive for severity of eye phenotype or systemic involvement, and vice versa, with significant phenotypic variability being observed. 9 We observed intrafamilial and interfamilial aniridia phenotype variability. The rest of the missense mutations were associated with a milder ocular phenotype.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The conclusion is that the iris malformations in these patients may be due to mutation in another gene that has a role in the formation of the eye, and thus aniridia is phenotypically present (9). This has been supported by results of the study which showed that mutations in the CYP1B1 gene can lead to the appearance of congenital aniridia and glaucoma (10).…”
Section: Discussionmentioning
confidence: 78%
“…On the other hand, studies performed in China (8) and Poland (9), highlight deletions of different scope in coding regions of the PAX6 gene as the main cause of aniridia.…”
Section: Discussionmentioning
confidence: 99%